Sequence typing of Haemophilus ducreyi isolated from patients in the Namatanai region of Papua New Guinea: Infections by Class I and Class II strain types differ in ulcer duration and resurgence of infection after azithromycin treatment. - Monica Medappa; Petra Pospíšilová; Lucy N John; Camila González-Beiras; Marti Vall-Mayans; Oriol Mitjà; David Šmajs (Public Library of Science (PLoS), 2024)
Haemophilus ducreyi (HD) is an important cause of cutaneous ulcers in several endemic regions, including the Western Pacific Region, especially among children. An HD sequence typing on swab samples taken from 1,081 ulcers in the Namatanai district of Papua New Guinea, during the pilot study for treatment of yaws, has been performed using the Grant typing system. Of the 363 samples that tested positive for the 16S rDNA of HD, the dsrA sequences of 270 samples were determined. Altogether they revealed 8 HD strain types circulating in Namatanai, including seven strain types of Class I (I.3, I.4, I.5, I.9, I.10, I.11, I.12) and one strain of Class II (II.3); four Class I types (I.9, I.10, I.11, I.12) were novel. The southern region of Namatanai (Matalai Rural) was identified as the region with the lowest genotype diversity and with most infections caused by HD Class II. The middle and northern subdistricts were affected mainly by HD Class I. Analysis of patient characteristics revealed that Class II HD infections were more often represented by longer-lasting ulcers than Class I HD infections. An increase in the prevalence of the I.10 strain was found after azithromycin administration compared to the untreated population at baseline likely reflecting higher infectivity of HD Class I, and more specifically strain type I.10.